Susceptibility Testing with the Manual Mycobacteria Growth Indicator Tube (MGIT) and the MGIT 960 System Provides Rapid and Reliable Verification of Multidrug-Resistant Tuberculosis - Ådjers-Koskela, Kati (American Society for Microbiology, 2003)
The objective of the study was to compare the manual Mycobacteria Growth Indicator Tube (MGIT) method and the BACTEC MGIT 960 system to the BACTEC 460 method for susceptibility testing of Mycobacterium tuberculosis. The evaluation was based on testing of 36 M. tuberculosis strains with various susceptibilities to isoniazid (INH), rifampin (RMP), ethambutol (EMB), and streptomycin (SM). In addition, five of the strains generating discrepant results in testing for EMB were analyzed for heteroresistance. For INH, the susceptibility test results obtained by the MGIT 960 and the manual MGIT systems agreed with the BACTEC 460 results in 94 and 97% of the cases, respectively. The results of susceptibility to RMP were all in agreement. For SM, 78 and 72% of the results obtained by the MGIT 960 and the manual MGIT systems, respectively, agreed with the BACTEC 460 results. In contrast, less than 80% of the results for susceptibility to EMB obtained by the two MGIT methods agreed with the BACTEC 460 results. All five strains analyzed for EMB heteroresistance were found to consist of resistant and susceptible subpopulations. The average turnaround times were 6.4 days for the MGIT 960 system, 6.5 for the manual MGIT system, and 8.7 days for the BACTEC 460 method. Both MGIT methods can be regarded as accurate and rapid alternatives to the BACTEC 460 method for detection of strains resistant to INH and RMP. However, more studies are needed for solving the problems associated with susceptibility testing to EMB and SM.